Present Peace, Future Freedom: Children’s Meditation Instruction in Two Diasporic Tibetan Buddhist Lineages - Emory-Moore, Christopher (Religious studies and theology, 2020)
Euro-North American Buddhism consists of a diversity of transplanted Asian traditions whose cultural adaptations often include heightened emphases on both family and meditation. This paper considers the nexus of these two themes in an examination of children’s meditation instruction in two of the largest international Gelukpa Tibetan Buddhist networks, the Foundation for the Preservation of the Mahayana Tradition (FPMT) and the New Kadampa Tradition (NKT). Through a comparison of these organizations’ recently published English-language children’s meditation manuals, the paper aims to produce a clearer picture of how children and their capacities for meditation are being conceptualized and cultivated in diasporic Tibetan Buddhist formations. I argue that the texts of the FPMT and NKT reflect respectively enthusiastic and measured approaches to the adaptation of Gelukpa Tibetan Buddhist meditation’s traditional doctrinal context and goals for primarily non-Tibetan audiences.